2019
DOI: 10.1111/vco.12488
|View full text |Cite
|
Sign up to set email alerts
|

Expression and the molecular forms of neutrophil gelatinase‐associated lipocalin and matrix metalloproteinase 9 in canine mammary tumours

Abstract: Neutrophil gelatinase‐associated lipocalin (NGAL) is a new biomarker for renal injury. It is also involved in tumorigenesis of different human cancer types. The oncogenic role of NGAL is related to its molecular forms, and heterodimer formation with matrix metalloproteinase 9 (MMP9) promotes human breast cancer (HBC) invasion and metastasis. To date, the levels of NGAL and NGAL/MMP9 complex have not yet been explored in canine mammary tumours (CMTs). Hence, this study aimed to investigate whether NGAL and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…NGAL expression is regarded as a considerable diagnostic and prognostic biomarker in several diseases, including inflammation and tumor growth (29,31,34). It is noteworthy that NGAL generates a complex with metalloproteinase-9 (MMP-9) that constraints MMP-9 autodegradation and subsequently leads to increased activity of MMP-9 (31,(34)(35)(36). Previous studies have suggested that MMP-9/NGAL complex augments cancer growth, including breast cancer (29,31,(34)(35)(36).…”
Section: Determination Of Fabp4 Rbp4 and The Mmp-9/ngal Complex In Tmentioning
confidence: 99%
See 2 more Smart Citations
“…NGAL expression is regarded as a considerable diagnostic and prognostic biomarker in several diseases, including inflammation and tumor growth (29,31,34). It is noteworthy that NGAL generates a complex with metalloproteinase-9 (MMP-9) that constraints MMP-9 autodegradation and subsequently leads to increased activity of MMP-9 (31,(34)(35)(36). Previous studies have suggested that MMP-9/NGAL complex augments cancer growth, including breast cancer (29,31,(34)(35)(36).…”
Section: Determination Of Fabp4 Rbp4 and The Mmp-9/ngal Complex In Tmentioning
confidence: 99%
“…It is noteworthy that NGAL generates a complex with metalloproteinase-9 (MMP-9) that constraints MMP-9 autodegradation and subsequently leads to increased activity of MMP-9 (31,(34)(35)(36). Previous studies have suggested that MMP-9/NGAL complex augments cancer growth, including breast cancer (29,31,(34)(35)(36). MMP-9 is found in gelatinase granules and contribute to cancer progression, invasion and metastasis in numerous neoplastic diseases (29,37,38).…”
Section: Determination Of Fabp4 Rbp4 and The Mmp-9/ngal Complex In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 2019 (10) found that malignant canine breast tumors express MMP-9 at a higher rate than normal breast tissues. Nowak et al 2008 (29) detected MMP-9 positive reaction in 83% of the cases in their study with tissue samples taken from 35 canine mammary carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, studies indicate that accumulation of NGAL is associated with the progression of the tumor (Fernandez et al, 2005;Provatopoulou et al, 2009). Three molecular forms of NGAL complexed with Matrix Metalloproteinase 9 (MMP9) are identified which are monomer (25-kDa), homodimer (45-kDa) and heterodimer (135-kDa) (Chen et al, 2019). MMP9 is an enzyme which participates in the initiation, growth, metastasis, and progression of the tumor (Gialieli et al, 2011).…”
Section: Neutrophil Gelatinase-associted Lipocalin and Matrix Metalloproteinase 9 Complexmentioning
confidence: 99%